Mental health of mothers who gave birth immediately after the Great East Japan Earthquake and behavioral problems of their children: a 5-year follow-up study focusing on the pregnancy trimester at the time of the disaster - 柿坂 佳菜恵; 山家 健仁; 千葉 柊作; 松尾 菜津美; 吉岡 靖史; 内出 希; 八木 淳子; 大塚 耕太郎 (Journal of Iwate Medical Assiociation, 2024)
There have been many reports on the effects of disasters on children and their caregivers. However, there have been very few reports on the emotions and behavioral effects on children who were born immediately after the disaster and not directly affected. Therefore, we studied the relationship between the behavioral problems in such children several years after birth, the mental health of their caregivers, and the damage and conditions related to disaster, focusing on the pregnancy trimester at the point of the disaster. The subjects were children who were born within 1 year of the earthquake and their caregivers, and analyses were made based on 3 classifications: prenatal, first trimester, and second and third trimesters of pregnancy. We found few behavioral problems in children in the first trimester group. In addition, the relationship between the environmental factors before and at the time of the disaster, the mental health of the caregivers, and the behavioral problems in children differed according to the pregnancy trimester. The findings in this study highlight the importance of focusing on the pregnancy trimester during such major disasters and could lead to improved support for children who were born within 1 year of the disaster.